(untitled) (American Journal of Islam and Society, 2007)
In recent years, more has been written about jihad than any other single topic related to Islam. Faisal Devji tries to shed light on the people behind the slogans, documents concerning terrorism, and their inner logic by analyzing the writings, interviews, and communiqués of Osama bin Laden and Ayman al- Zawahiri, as well as the will of Muhammad Atta (pp. 113-15). These and other illustrations clearly reflect the ideological viewpoint of the “jihadists.” This book, an interesting historical and cultural analysis of the so-called “jihadi” movement and its representatives today, focuses on the globalization of jihad’s moral and aesthetic dimensions. The author deals with its conceptual landscapes, namely, al-Qaeda’s models of belief and action. In his preface, Devji suggests that both the 1998 terror attacks against the American embassies in Dar al-Salaam and Nairobi and 9/11, all undertaken by al- Qaeda, turned jihad into a global weapon of spiritual conflict. Thus, its focus has extended far beyond its original struggle against the Soviet occupation of Afghanistan. Devji explains: “Two factors make the Jihad into a global movement: the failure of local struggle and the inability to control a global landscape of operations by the politics of intentionality” (p. 31) ...